Family planning use among young mothers in the peri-urban area of Osun State, Nigeria: the influence of spousal communication and attitude - Obasanjo Afolabi Bolarinwa; Akintayo Taiwo Olaniyan; Balsam Qubais Saeed; Olalekan Seun Olagunju (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - The purpose of this study is to examine the influence of spousal communication and attitude toward family planning (FP) use among young mothers in the peri-urban area of Osun State, Nigeria. Design/methodology/approach - The study was limited to a primary cross-sectional dataset collected among 420 young mothers between the ages of 15 and 30 years residing in the peri-urban area of Osun State, Nigeria. The distribution of the use of FP across the socio-demographic, spousal communication and attitude was described, and multivariate logistic regression was used to assess FP use likelihood. The results were presented as crude odds ratios (cOR) and adjusted odds ratios (aOR) with their corresponding 95% confidence intervals. Statistical significance was set at p-value < 0.05. Findings - FP use were more likely to be higher among the respondents whose male spouses have good communication [cOR = 35.5; 95% (15.93-78.99)], good attitude [cOR = 8.6 95% (3.59-20.65)] and this persisted after adjusting for significant covariates [aOR = 80.7; 95% (19.80-328.84)] and [aOR = 5.4 95% (1.34-22.17)]. Research limitations/implications - The study's strength is the ability to design questionnaires tailored toward the literature gap on nonuse of FP by young mothers. However, the study is without limitation because the focus was on young mothers alone why their spouses were not interviewed. Male spouse details were collected from the young mothers, and there may be inaccuracy in the reporting of male spouse socio-demographic characteristics used as a control variable in this study. Also, because this research was conducted among specific group, the results of the study cannot be used to generalize for other group. Practical implications - Future studies should consider both partners to harness the true picture of poor communication and attitude toward each other. The future study will also be more robust if it can consider a qualitative research design as this will help unveil more underlining factors influencing the nonuse of FP among young mothers. Originality/value - Young mothers with good spousal communication and attitude were more likely to use FP. Deliberate interventions should include focus group discussion and community sensitization to encourage good communication and attitude of male spouse toward their partner in the peri-urban area of Osun State, Nigeria.